1970
DOI: 10.3133/twri05a1_1970
|View full text |Cite
|
Sign up to set email alerts
|

Methods for collection and analysis of water samples for dissolved minerals and gases

Abstract: The Department of the Interior has a basic responsibility for the appraisal, conservation, and efficient utilization of the Nation's natural resources including water as a resource as well as water involved in the use and development of other resources. As one of the several Interior agencies, the U.S. Geological Survey's primary function in relation to water is to assess its availability and utility as a national resource for all uses. The Geological Survey's responsibility for water appraisal includes not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The EC and TDS are highly correlated to each other. 10,62,63 In the study area, EC and TDS were found to decrease in the following order: S4 > S3 > S5 > S1 > S2 > S7 > S8 > S6 (shown in the spatial variation map in Figure 2). EC and TDS were found to be maximal in the industrial region compared to the residential area.…”
Section: Resultsmentioning
confidence: 90%
“…The EC and TDS are highly correlated to each other. 10,62,63 In the study area, EC and TDS were found to decrease in the following order: S4 > S3 > S5 > S1 > S2 > S7 > S8 > S6 (shown in the spatial variation map in Figure 2). EC and TDS were found to be maximal in the industrial region compared to the residential area.…”
Section: Resultsmentioning
confidence: 90%